Susceptibility to multiple sclerosis is associated with the proximal immunoglobulin heavy chain variable region. - Walter, M A (1991)
15 immunoglobulin heavy chain constant (CH) and variable region (VH) polymorphisms were selected to span the entire length of the heavy chain cluster. These polymorphisms were examined in 34 sib pairs concordant for multiple sclerosis (MS) and in 23 sporadic MS patients. Allele frequencies were calculated for the 2 MS patient groups and compared with those found in a control population from the same geographical location and of similar ethnic background. No significant association was found between MS and the 7 CH region polymorphisms examined. However, a significant correlation between the MS phenotype and a VH2 family polymorphism was observed in both MS patient populations (familial MS patients chi 2 = 8.16, P less than 0.005; sporadic MS patients chi 2 = 8.90, P less than 0.005). One allele of the VH2-5 gene segment was found to be over-represented in both MS groups. VH2-5 has recently been physically mapped close to the CH region, between 180 and 360 kb away. These results indicate that a locus near or within the CH-proximal VH region is associated with increased susceptibility to MS.